Pengaruh Influencer Devi Purnamasari terhadap Perubahan Gaya Berpakaian Para Pengikutnya - Zerlynda Ali; Hudi Santoso; Suparman; Nabila Manisya; Anggi Widya Khairunisa; Khalila Zahra (Bahasa Indonesia, 2025)
The digital era has made social media the primary platform influencing people's lifestyles, particularly through the role of influencers in promoting fashion trends. This study aims to analyze the influence of Devi Purnamasari's Instagram content on changes in her followers' dressing styles and identify factors affecting these changes. The research method uses a quantitative approach with online surveys of 45 female respondents following @purnamasari_devi aged 18-45 years, using simple random sampling technique and Slovin formula with 15% margin of error. Data were analyzed using the AISAS model (Awareness, Interest, Search, Action, Share) for independent variables and Kotler & Keller's lifestyle theory for dependent variables. Results show significant influence of Devi Purnamasari's content on followers with high awareness levels (26.89), positive interest (25.60), strong adoption of dressing styles (32.31), and good content sharing (30.29). Changes in dressing lifestyle manifest through positive dressing habits (24.42), high preferences (30.47), and active engagement (52.58). The study concludes that influencers have a transformative role in shaping the dressing lifestyle of digital communities, providing important implications for influencer-based marketing strategies in the fashion industry.